2008
DOI: 10.1016/j.ajog.2007.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Elevated asymmetric dimethylarginine concentrations precede clinical preeclampsia, but not pregnancies with small-for-gestational-age infants

Abstract: Objective-The purpose of this study was to investigate maternal plasma concentrations of asymmetric dimethylarginine (ADMA) in mid-pregnancy and at the time of disease in women who develop preeclampsia compared to women with uncomplicated pregnancies and women with SGA infants.Study design-Plasma samples were collected at mid-pregnancy and at the time of delivery from 31 women with uncomplicated pregnancies, 12 women with SGA infants and 15 women with preeclampsia. ADMA and L-arginine were measured by high-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 27 publications
2
43
1
3
Order By: Relevance
“…Elevated maternal L-arginine concentrations have been previously found in preeclampsia (18), as we found in our study, but other studies have shown unchanged (15,17,19) or lower concentrations (16) compared with controls. It has been argued that the L-arginine/ADMA ratio, rather than ADMA levels, is the key determinant of NOS activity (10), which is regarded as a useful index for interpretation of ADMA's effects (11).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Elevated maternal L-arginine concentrations have been previously found in preeclampsia (18), as we found in our study, but other studies have shown unchanged (15,17,19) or lower concentrations (16) compared with controls. It has been argued that the L-arginine/ADMA ratio, rather than ADMA levels, is the key determinant of NOS activity (10), which is regarded as a useful index for interpretation of ADMA's effects (11).…”
Section: Discussioncontrasting
confidence: 49%
“…There have been discrepant findings of elevated (15) and unchanged (16,17) ADMA concentrations in the maternal circulation in women with preeclampsia compared with women with uncomplicated pregnancies. Elevated maternal ADMA concentrations have been found preceding the clinical symptoms of preeclampsia (18,19) suggesting that ADMA could have a role in the pathogenesis of preeclampsia.There are sparse data on fetal concentrations of ADMA and its associated molecules in pregnancy and preeclampsia (20). The aim of this study was to simultaneously explore maternal and fetal concentrations of L-arginine, ADMA, and SDMA in preeclampsia and possible associations of these measurements with gestational characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,17,[23][24][25][26][27][28][29][30][31][32][33] Because NO is an important physiological vasodilator in normal pregnancy, it follows that NO deficiency during preeclampsia has been implicated in the disease process. 18,[23][24][25][26][27][28][29][30][31][32][33] Although numerous studies indicate chronic NOS inhibition in pregnant rats produces hypertension associated with peripheral and renal vasoconstriction, proteinuria, intrauterine growth restriction, and increased fetal morbidity, 11,12,25 it is unclear whether an NO deficiency occurs in women with preeclampsia. Much of the uncertainty in this area of research originates from the difficulty in directly assessing the activity of the NO system in the clinical setting.…”
Section: Potential Mediators Of Endothelial Dysfunction Nitric Oxidementioning
confidence: 99%
“…24,26 -28 Elevated asymmetrical dimethylarginine (ADMA) concentration before clinical onset of preeclampsia also suggests a role of this NO synthase inhibitor in the pathophysiologic condition of preeclampsia. 26 The activity of the NO system has also been assessed in animal models of placental ischemia and cytokine excess. Placental ischemia in pregnant rats has no effect on urinary nitrite/nitrate excretion relative to control pregnant rats.…”
Section: Potential Mediators Of Endothelial Dysfunction Nitric Oxidementioning
confidence: 99%